Implementation of Arabic Online Learning at Post-Pandemic of Covid 19 - Aceng Rahmat; Mohammad Sarip; Khambali Khambali; Mohammed Alghali Khalil Yusuf (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2023)
Entering the 21st century, education is using technology massively in learning activities, especially during the COVID-19 pandemic, so online learning is born with a variety of models and platforms. Online learning is generally divided into two categories: MOOCs (massive open online courses) and LMSs (learning management systems). This study aimed to show how online learning is built and how it can be implemented into different learning models. The study used descriptive qualitative research aimed at revealing the phenomenon of the preparation and implementation of online Arabic learning post-COVID-19 pandemic, based on data obtained from various literature and observations. The results revealed that in order to build and implement online Arabic language learning, the first research was carried out in the form of RPS and textbooks in PDF and/or video formats so that the material could be integrated into the online platform, and then the implementation of online learning could be in different models, whether blended, hybrid, or flipped, depending on the learning model structured in the planning document.